Thackeray and Form of Fiction - Loofbourow, John (Book collections on Project MUSE., 1964)
In a critical examination of Thackeray's style, Mr. Loofbourow shows how Thackeray "hybridized" the genre of the romance by adapting the tone and language of the epic, the chivalric romance, and the pastoral, and by carrying parody and satire to a high technical level. Thackeray used these techniques with particular success in Vanity Fair and Henry Esmond. Besides analyzing these two works, Mr. Loofbourow discusses the significance of epic in the 19th century, the expressive values of the novel as a whole, and the relevance of Thackeray's methods to the work of such writers as George Eliot, Henry James, Virginia Woolf, and E.M. Forster. His book is an attempt to come to terms with Thackeray's style, and a work conceivably destined to become a landmark among the very few acceptable studies of English fiction. It should prove indispensable to anyone interested in style in fiction, and should at the same time precipitate a new trend in Thackeray scholarship. Originally published in 1964. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.